ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN MINYAK GORENG CURAH - Delima, Sri (Agriprimatech, 2020)
“Analysis Of Factors Which Influence Consumers In Making Decision Purchase Oil Fry Bulk in Subdistrict Pantai Cermin.( Study Case : Housewives Appliances in Subdistrict Pantai Cermin" this research is guided by Myrna Pratiwi Nasution SP., MP . The purpose of research it is to identify the characteristics of consumers of oil fry bulk location research , identify the decision -making of consumers in buying the product oil fried bulk and to determine the factors that influence on the decisions of consumers in the purchase of the product oil cooking of the samples performed by using the technique of purposive sampling with a sample of 100 respondents . The method of analysis that is used is the method of analysis of descriptive , analytical factors, multiple reservation the data supported by Microsoft Excel 2013 and statistical package of social science (SPSS) version 21. The research is conducted on the month in March -April 2020. The results of the study it can be concluded that (1) consumers of oil fried output is dominated by the age of 31-40 years (67 %), most large has a background of education junior high school (73%), clarification of the work of consumers on average mother house of stairs (100%). (2) the process of making the decision of purchase of consumer oil fried bulk through the five stages of the process are : introduction to the problem, the search for information , alternative evaluations , purchasing decisions , post- purchase behavior ; (3) the results of the analysis of the factors that the seven factors that are culture factors, social factor, personal culture of social factors, social psychological factors, psychological factors, culture factors, culture psychological factors. Key Word : Oil Fry Bulk, Analysis Factor.